2016
DOI: 10.1007/s00425-016-2598-z
|View full text |Cite
|
Sign up to set email alerts
|

Stilbene accumulation and expression of stilbene biosynthesis pathway genes in wild grapevine Vitis amurensis Rupr.

Abstract: We detected and quantified six stilbenes ( cis -piceid, t -piceid, t -ε-viniferin, cis -ε-viniferin, t -resveratrol, and t -δ-viniferin) in the leaves, petioles, berry skins, and seeds of wild-growing Vitis amurensis . The highest content of stilbenes and expression of stilbene biosynthesis genes were in the probes collected in the autumn and after ultraviolet elicitation. Stilbenes, including the best-studied stilbene resveratrol, are known to display valuable bioactivities and protect plants against various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 44 publications
2
49
0
1
Order By: Relevance
“…Grapevine is an important source of bioactive stilbenes . Therefore, in this study, we examined the influence of plant phenolic precursors, Cin and Caf acids, on stilbene production and STS gene expression in grapevine callus cultures.…”
Section: Resultsmentioning
confidence: 99%
“…Grapevine is an important source of bioactive stilbenes . Therefore, in this study, we examined the influence of plant phenolic precursors, Cin and Caf acids, on stilbene production and STS gene expression in grapevine callus cultures.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies show that UV-C light exposure induced stilbene biosynthesis in different plant species (e.g., grapevine, pine, peanut, and gnetum), and the induction was accompanied by a transcriptional activation, protein accumulation, and enzyme activation of STS and some other stilbene biosynthesis enzymes (Wang et al 2010Tang et al 2010;Suzuki et al 2015;Deng et al 2016Deng et al , 2017Kiselev et al 2017). For grapevine berries, it has been shown that the induction of resveratrol biosynthesis after UV-C irradiation occurred primarily in the form of t-resveratrol (not piceids) and was dependent on the berry developmental stage .…”
Section: Biotic and Abiotic Stresses As Regulators Of Stilbene Biosynmentioning
confidence: 99%
“…The analysis of qPCR data was performed using the 2 −ΔΔCT method (Livak and Schmittgen 2001) with two endogenous controls for cDNA normalization (AtActin2, GenBank NM_112764 and AtGAPDH, GenBank NM_111283, Kiselev et al 2017). The data shown were obtained from three independent experiments and are averages of eight technical replicates for each independent experiment (four qPCR reactions normalized to Actin and four qPCR reactions normalized to GAPDH expressions for each independent experiment).…”
Section: Extraction Of Rna and Reverse Transcription (Rt) Real-time Qmentioning
confidence: 99%